Kompetensi Manajerial Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di Madrasah Aliyah Negeri (MAN) 4 Kebumen - Dian Inugrah Wijayanti (LPPM IAINU Kebumen, 2019)
The quality of education can be said to be a picture of the merits of a school. Schools are considered qualified if they succeed in achieving their educational goals. Related to the effectiveness of educational goals, the managerial competence of madrasa heads plays a very important role. This research observes a link between managerial competence and the quality of education so that the problem in this research can be formulated as follows, How is the Managerial Competence of Madrasah Principals in Improving the Quality of Education in State Madrasah Aliyah (MAN) 4 Kebumen? This type of research is qualitative research. There are two kinds of data sources in this study, namely primary data sources and secondary data sources. Primary data sources include subjects, namely school principals, teachers and staff of MAN 4 Kebumen employees, while secondary data sources include documents, written notes related to the research focus. Data collection techniques by way of interviews, observation, and documentation. The data obtained during the research were analyzed by means of data reduction, data presentation, and conclusion drawing. While the data validity test was carried out with persistence and triangulation observations. The triangulation used in this research is source triangulation. The results of this study indicate that the managerial skills of the Madrasah MAN 4 Kebumen in improving the quality of education have several indicators, namely, Technical Skills, Human Skills, Conceptual Skills. (1) In mastering the technical skills of the madrasah principal to improve the quality of education the madrasah principal is armed with his experience through the trainings he attends and the madrasah principal makes use of school facilities and infrastructure such as the use of LCDs during learning. (2) The madrasa principal's human relations skills in improving the quality of education are reflected in establishing effective communication with teachers. (3) The conceptual skill of the madrasa head in improving the quality of education is by carrying out clear planning contained in the vision, mission and objectives of the madrasa.